Application of 3D GIS flood simulation to investigate the source of inundation at Pekan sub-district - Shammodin, Muhammad Shaheed; Ahmad, Zuhairi; Singh, Ranjit (Akademi Sains Malaysia, 2019)
Flood is usually caused by heavy precipitation that eventually lead to river spillage. In some rare cases, inundation could happen due to the accumulation of water on land cover resulting in stagnant flooding. Pekan sub-district is chosen as the ideal study area to determine the type of flood in this location. Using Geographic Information System (GIS) approach, 3-Dimensional inundation simulation procedure is applied to discover the real source of flooding at the study area. This study is performed to observe flood pattern over the study area based on the river surface level readings of nearby Department of Irrigation and Drainage Malaysia (DID) station. Flood simulation used SRTM (Shuttle Radar Topographic Mission) dataset to produce Pekan sub-district topography into 3D TIN (triangulated irregular network) model. Additionally, water body layer represents specific Pahang River gauge level offsets for overland inundation and river expansion inspection. Historical datasets of Pahang River hydrograph at station 3434401 published by DID were used to find the peak level. Results from inundation model instances show that very few overtopping incidences observed along Pahang River within the study boundary. Still, signs of the growing number of water spots on land cover positively indicate that inundation is again happening. This situation concludes that Pekan sub-district flood occurrences are caused by stagnant flooding. Justification is done through photographic evidence and historical DID hydrograph datasets of the year 2007 to the 1st quarter of 2018.